2019
DOI: 10.1177/1120672119865699
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of small incision lenticule extraction versus advanced surface ablation in low myopia

Abstract: Purpose:To compare the visual and refractive outcomes of small incision lenticule extraction and advanced surface ablation for low myopia or myopic astigmatism.Methods:Retrospective, observational case series of our first 50 consecutive small incision lenticule extraction patients compared to refraction-matched 50 advanced surface ablation treatments with attempted spherical equivalent correction ⩽−3.5 D, astigmatism ⩽−1.5 D, and corrected distance visual acuity of 1.0 (decimal scale) or better. Only one eye p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…This is because of our tendency for undercorrection when preoperative TCT is below 500 µm and it is a priority to not exceed the limits for residual stromal thickness. When the patients with targeted undercorrection are left out, the efficacy index (0.99 ± 0.13) is comparable with other studies [30][31][32], which report results of SMILE for corneas with central CCT of 550 ± 30 in low to moderate myopia. So this residual SE refraction does not deteriorate the uncorrected distance visual acuities of the participants and does not reduce the efficacy of this procedure for thin corneas if only it is less than 0.75 D.…”
Section: Discussionsupporting
confidence: 84%
“…This is because of our tendency for undercorrection when preoperative TCT is below 500 µm and it is a priority to not exceed the limits for residual stromal thickness. When the patients with targeted undercorrection are left out, the efficacy index (0.99 ± 0.13) is comparable with other studies [30][31][32], which report results of SMILE for corneas with central CCT of 550 ± 30 in low to moderate myopia. So this residual SE refraction does not deteriorate the uncorrected distance visual acuities of the participants and does not reduce the efficacy of this procedure for thin corneas if only it is less than 0.75 D.…”
Section: Discussionsupporting
confidence: 84%
“…Ang et al [19] pointed out that, one year after SMILE, in 98.0% of cases, the CDVA was equal to or better than that before surgery, and the efficacy index was 0.99±0.20. In Taneri et al's [28] study, at 3mo after SMILE surgery 96.0% cases had CDVA equal or better than before the surgery, and the mean efficacy index was 1.03. Our results reported that the data was 98.8% 6mo after SMILE surgery, and the efficacy index was 1.05, both similar to previous results, thereby confirming the safety and efficacy of SMILE in correcting myopia refractive error in adults.…”
Section: Discussionmentioning
confidence: 89%
“…The study sample size was based on the postoperative uncorrected distance visual acuity (UCVA). In this study, a UCVA difference of 0.096 logMAR will be considered clinically meaningful and the standard deviation of postoperative UCVA is about 0.12 based on previous studies [ 10 , 11 ]; thus, a total sample size of 117 eyes (39 eyes per group) will be needed for 5% significance and 80% power. Participants were randomly allocated to groups A–C in a ratio of 1:1:1.…”
Section: Methodsmentioning
confidence: 99%